GAMBARAN TINGKAT KEPUASAN WISATAWAN ASING TERHADAP MUTU PELAYANAN KESEHATAN GIGI DAN MULUT DI BALI DENTAL CLINIK 911 DENPASAR TAHUN 2020 - I Nyoman Gejir; Ida Ayu Dewi Kumala Ratih; Ni Nengah Sumerti; Dewa Ayu Perawati (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2021)
Bali Dental Clinic 911 is Dental and Oral Health Service which located in Denpasar. The kind of service in the Clinic, include; preventive, kurative, and rehabilitave in dental health, for Indeonesian and foreigns.The data shows that patients visiting in 2016 are 5,043, in 2017 are 5,830, and in 2018 are 6,350, majority patients from Austria. The goals of this research is to know the descriptive of satisfaction of foreigns tourism toward dental and oral services in Bali Dental Clinic 911 in 2020. This is a descriptive research with survey. The respondents in this research were all foreigns tourism who were visit Bali Dental Clinic 911 Denpasar in March 2020, with the total number of respondents are 50.The result of this research shows that: reliability demention with very satisfaction (91,5%), Responsiveness demention with very satisfaction (87,3%), assurance demention with very satisfaction (92%), Emphaty demention with very satisfaction (90%), tangibles demention with very satisfaction (85%). The conclussion of this research shows that majority foreigns tourism who were visit Bali Dental Clinic 911 Denpasar in March 2020 got very satisfaction services in dental and oral health